Monitoring Electrical Charge Overflow During Voltage Conditions as a Preventive Measure for Preventing Disturbances in 20kv Feeder at PT PLN (Persero) ULTG Nias - Roy Christian Siregar; Hamdani Hamdani; Siti Anisah (INFOKUM, 2026)
The reliability of 20 kV feeders is greatly influenced by the condition of the equipment and the insulation system that operates continuously. One of the causes of disturbances in the distribution network is the occurrence of electrical overflow (partial discharge) which can develop into equipment damage if not detected early. This study aims to analyze the application of electrical overflow monitoring during voltage conditions as a preventive measure to prevent disturbances in 20 kV feeders at PT PLN (Persero) ULTG Nias. The research method was carried out through online partial discharge measurements using the Ultra TEV Plus 2 tool in the GB2, GB3, and GB4 feeder cubicles without performing a system shutdown. The data obtained were analyzed based on the parameters of Transient Earth Voltage (TEV), Pulse Per Cycle (PPC), and ultrasonic measurements to determine the level of potential disturbances in the equipment. The measurement results showed that the GB2 and GB3 feeders had a TEV value of 5 dB with a PPC of 0 so that they were included in the normal category and did not show any indication of partial discharge activity. Meanwhile, on the GB4 feeder, a TEV value of 20 dB with a PPC of 1.83 was obtained, and a hissing sound was detected in ultrasonic measurements, indicating the presence of medium-level partial discharge activity due to a decrease in insulation quality. The results of the study prove that monitoring electrical discharge overflows under voltage conditions can identify potential disturbances early so that maintenance actions can be carried out appropriately and planned to improve feeder reliability and maintain the continuity of electricity distribution.